Penerapan Media Pembelajaran Interaktif dalam Pengenalan Komunikasi Inggris Berbasis Macromedia Flash SMK Negeri 4 Palembang - Uzer, Yuspar; Jaya, Aswadi; Uzer, Yus Vernandes; M, Marleni; H, Herlina; H, Hermansyah; Mortini, Asti Veto (Yayasan Daarul Huda Kruengmane, 2025)
This dedication to the community is done as an embodiment of the implementation of Tri Dharma College Lecturer University PGRI Palembang and L2 Dictionary Palembang. The goal to be achieved by the implementation of this Community Service (CSR) is that the lecturers can apply and develop the academic skills they have, in addition after following this training the students are expected to be able to perform so that the students speak English directly. communicative and intelligent in the use of English with the title Application of Interactive Learning Media in the Introduction of Macromedia-Based English Communication Flash SMKN 4 Palembang.